Secondary outcomes of the guided self-help behavioral activation and physical activity for depression trial. (4th July 2019) - Soucy, Isabelle; Provencher, Martin D.; Fortier, Michelle; McFadden, Taylor
Abstract: Background: This article presents secondary outcome variables from a randomized controlled trial evaluating the efficacy of two guided self-help interventions for the treatment of depression: behavioral activation (BA) and physical activity (PA). Both interventions resulted in significant reductions in depressive symptoms compared to the wait-list control group, however the mechanisms by which these interventions influenced depression were not presented. Purpose: The purpose of this paper was to compare changes in secondary outcome variables to gain insight into the mechanisms by which reactivation interventions reduce depressive symptoms. Results: Mixed-model analysis of variances (ANOVAs) revealed significant increases in life satisfaction (Main effect: F(3, 91.71)  = 4.63, p  < 0.01) and self-efficacy (Main effect: F(3, 91.32)  = 4.05, p  < 0.01) as well as significant decreases in negative affect (Main effect: F (2, 75.88)  =  5.24, p  < 0.01) and loneliness (Main effect: F (2, 71.78)  =  7.49, p  < 0.01) in both interventions at pre-, mid-, post-intervention and follow-up. The group x time interactions were not significant, suggesting that the PA and BA interventions had comparable effects over time. Conclusion: These findings provide insight into the potential mechanisms underlying the effectiveness of guided self-help PA and BA interventions on depressive symptoms.